Legal Relations and Legal Consequences of Wakalah Contract Implementation in Hajj Fund Deposit - Dewi Nurul Musjtari; Syintia Widya Kencana (Universitas Ahmad Dahlan, 2020)
Introduction to The Problem: Hajj financial management in Indonesia is entrusted to the Hajj Financial Management Agency (BPKH). The central point of controversy is whether or not a portion of the Hajj deposit funds are legally permitted to finance a government infrastructure program. Another problem that emerges in the controversy is the spreading issue regarding the obligation of candidates of the pilgrims of signing the WakÄlah (agency) contract for the Hajj registration. It is assumed that the candidates must agree when the BPKH invests the Hajj fund in the infrastructure program.Purpose/Objective Study: To analyze the legal relationship between Muwakkil (the principal) and Wakil (the agent) on the implementation of the WakÄlah Contract for the pilgrimage fund deposit, categorizing the contract and the legal consequences of the use of hajj funds that are not following the purpose of the contract.Â Design/Methodology/Approach: The research method uses normative research with statutes and legal approaches to the WakÄlah contract. The technique of collecting data uses secondary data. Data were analyzed with qualitative descriptive.Findings: The legal relationship between the Muwakkil and the Deputy is based on the WakÄlah Agreement. The existence of WakÄlah contract in the Hajj fund deposit is a series with the aim of Muwakkil to run the Hajj. Therefore, the management of the hajj deposit funds should be based on applicable laws and regulations, the theory of authority, the theory of dispute resolution, and the purpose of the WakÄlah Contract. The Legal relationship and consequences if the use of the Hajj deposit funds contradicts existing laws and agreements and is not in accordance with the intended use, it can have consequences that the WakÄlah Contract will be null and void and if it contradicts the original agreement between Muwakkil and Wakiil then the Muwakkil can submit contract cancellation. In the event of a loss, the BPKH is responsible for compensating the Muwakkil in this case, the prospective pilgrims.Paper Type: Research Article.